2021
DOI: 10.3390/children8110970
|View full text |Cite
|
Sign up to set email alerts
|

Placental mTOR Signaling and Sexual Dimorphism in Metabolic Health across the Lifespan of Offspring

Abstract: Robust evidence of fetal programming of adult disease has surfaced in the last several decades. Human and preclinical investigations of intrauterine insults report perturbations in placental nutrient sensing by the mechanistic target of rapamycin (mTOR). This review focuses on pregnancy complications associated with placental mTOR regulation, such as fetal growth restriction (FGR), fetal overgrowth, gestational diabetes mellitus (GDM), polycystic ovarian syndrome (PCOS), maternal nutrient restriction (MNR), pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…As a nutrient sensor, mechanistic target of rapamycin (mTOR) has been implicated to be involved in the trajectory of fetal growth [23], and previous studies have demonstrated that mTOR activity is reduced [19,20,[24][25][26][27] or increased [28] in FGR placentae. While our placental staining confirmed the presence of mTOR and pS6 S240 in the human trophoblast cells [25,27,29], we observed no differences in mTOR protein expression, assessed both by IHC and western blotting, between our female AGA and FGR placentae.…”
Section: Discussionmentioning
confidence: 99%
“…As a nutrient sensor, mechanistic target of rapamycin (mTOR) has been implicated to be involved in the trajectory of fetal growth [23], and previous studies have demonstrated that mTOR activity is reduced [19,20,[24][25][26][27] or increased [28] in FGR placentae. While our placental staining confirmed the presence of mTOR and pS6 S240 in the human trophoblast cells [25,27,29], we observed no differences in mTOR protein expression, assessed both by IHC and western blotting, between our female AGA and FGR placentae.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise during pregnancy has been shown to be beneficial for both mother and child and may reduce the negative consequences of maternal obesity [15]. The placenta, which plays an essential role in nutrient transport and fetal growth, shows sexually dimorphic differences with maternal stressors, such as undernutrition and maternal obesity [38,39]. In this study, we investigated the influence of maternal EX on the placenta and potential mechanisms associated with maternal EX contributing to intrauterine effects, independent of maternal diet and/or weight changes in control-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR signaling is also shown to regulate the expression and localization of both amino acid ( Roos et al 2007 , 2009 a , b ) and glucose transport systems ( Buller et al 2008 ), likely impacting the flux of nutrients from mother to fetus. As such, evidence suggests that dysregulation of placental mTOR signaling in humans is associated with FGR and poor pregnancy outcomes ( Roos et al 2007 , Sati et al 2016 , Dimasuay et al 2017 , Beetch & Alejandro 2021 , Satterfield et al 2021 ). A recent study revealed a more direct association between placental mTOR and offspring metabolic health.…”
Section: Potential Mechanisms Of Placenta Mediated Beta-cell Developmentmentioning
confidence: 99%